UKM8032 microcontroller design and FPGA implementation by integrating DW8051 IP Core for SoC design - Chong, Victer; Othman, Masuri (Penerbit Universiti Sains Malaysia, 2004)
Microcontroller is an essential component for many general and application specific purposes such as airbag control system in automotive industry. Current applications of any microcontroller vary with larger size, higher cost, and lower processing speed yet not locally designed.